PASSIVE SURVEILLANCE AND RISK ANALYSIS OF GASTROINTESTINAL PARASITISM IN EQUINE POPULATION OF FAISALABAD METROPOLITAN, PAKISTAN - U. B. Tahir; M. S. Sajid; M. N. Khan; M. Saqib; R. M. Siddique; A. Qudoos (Journal of Animal and Plant Sciences, 2016)
A total of 3456 faecal samples of equines brought to the mobile clinic of the department of clinical medicine and surgery, University of Agriculture, Faisalabad, screened for gastrointestinal tract (GIT) parasitism using standard protocols. Information regarding possible risk factors was also collected with clinical observations on a predesigned questionnaire. A total of 45.1% (1562/3456) equines were recorded positive for GIT parasites in the study population. Younger, thinner, females, draught purpose animals and donkeys were found more prone to GIT parasitic infection, with highest rate of infection during summer. The results of this study will contribute towards the climatographic and quantitative distribution of GIT parasitism in equine population of Metropolitan city, Faisalabad, Pakistan.
Keywords: Epidemiology; Equine Faisalabad; Quantitative distribution; Gastrointestinal tract parasitism